‘Purest Bones, Sweet Remains, and Most Sacred Relics.’ Re-Fashioning St. Kazimierz Jagiellończyk (1458–84) as a Medieval Saint between Counter-Reformation Italy and Poland-Lithuania - Noyes, Ruth Sargent (Religions, 2021)
This article explores the Counter-Reformation medievalization of Polish-Lithuanian St. Kazimierz Jagiellończyk (1458-1484)—whose canonization was only finalized in the seventeenth century—as a case study, taking up questions of the reception of cults of medieval saints in post-medieval societies, or in this case, the retroactive refashioning into a venerable medieval saint. The article investigates these questions across a transcultural Italo-Baltic context through the activities of principal agents of the saint’s re-fashioning as a venerable saint during the late seventeenth century: the Pacowie from the Grand Duchy of Lithuania and the Medici from the Grand Duchy of Tuscany, during a watershed period of Tuscan-Lithuanian bidirectional interest. During this period, the two dynasties were entangled not only by means of the shared division of Jagiellończyk’s bodily remains through translatio—the ritual relocation of relics of saints and holy persons—but also self-representational strategies that furthered their religio-political agendas and retroactively constructed their houses’ venerable medieval roots back through antiquity. Drawing on distinct genres of textual, visual, and material sources, the article analyzes the Tuscan-Lithuanian refashioning of Kazimierz against a series of precious reliquaries made to translate holy remains between Vilnius to Florence to offer a contribution to the entangled histories of sanctity, art and material culture, and conceptual geography within the transtemporal and transcultural neocolonial context interconnecting the Middle Ages, Age of Reformations, and the Counter-Reformation between Italy and Baltic Europe.